Perinatal distress in 1p36 deletion syndrome can mimic hypoxic ischemic encephalopathy. Issue 8 (17th June 2019) - Carter, Lauren B.; Battaglia, Agatino; Cherry, Athena; Manning, Melanie A.; Ruzhnikov, Maura RZ; Bird, Lynne M.; Dowsett, Leah; Graham, John M.; Alkuraya, Fowzan S.; Hashem, Mais; Dinulos, Mary Beth; Vallee, Stephanie; et al.
Abstract: 1p36 deletion syndrome is a well‐described condition with a recognizable phenotype, including cognitive impairment, seizures, and structural brain anomalies such as periventricular leukomalacia (PVL). In a large series of these individuals by Battaglia et al., "birth history was notable in 50% of the cases for varying degrees of perinatal distress." Given the potential for perinatal distress, seizures and PVL, we questioned if this disorder has clinical overlap with hypoxic ischemic encephalopathy (HIE). We reviewed the medical records of 69 individuals with 1p36 deletion to clarify the perinatal phenotype of this disorder and determine if there is evidence of perinatal distress and/or hypoxic injury. Our data provides evidence that these babies have signs of perinatal distress. The majority (59% term; 75% preterm) needed resuscitation and approximately 18% had cardiac arrest. Most had abnormal brain imaging (84% term; 73% preterm) with abnormal white matter findings in over half of patients. PVL or suggestion of "hypoxic insult" was present in 18% of term and 45% of preterm patients. In conclusion, individuals with 1p36 deletion have evidence of perinatal distress, white matter changes, and seizures, which can mimic HIE but are likely related to their underlying chromosome disorder.